In vitro Plant Regeneration from Nodal Explants of Coleus forskohlii Briq. - An Important Medicinal Plant (Plant Tissue Culture and Biotechnology, 2020)
An efficient in vitro mass propagation and promising protocol has been successfully standardized and developed for Coleus forskohlii through direct organogenesis from nodal explants. Nodal explants cultured onto MS basal medium supplemented with 4.44 μM BAP recorded the highest response and produced 24.3 ± 0.2 shoots per explant with an average shoot length 5.6 ± 0.4 cm after 30 days of culture. The in vitro shoots recorded higher response for development of rooting on half strength MS fortified with 2.46 μM IBA which produced the best response 7.8 ± 0.6 roots per in vitro shoot with an average root length of 4.3 ± 0.1 cm after 25 days. The in vitro rooted plantlets were transferred for hardening and 90% of the plantlets survived were successfully acclimatized and established in small plastic pots. This protocol recorded to be a highly repeatable, successful and rapid technique that could be utilized for the commercial mass propagation and ex situ conservation of Coleus forskohlii. It is important to note that the morphology of the in vitro plantlets of Coleus forskohlii showed a true-to-type growth habit, both in vitro and when transferred to ex vitro growth conditions.Plant Tissue Cult. & Biotech. 30(1): 143-148, 2020 (June)